Satisfação com a amamentação entre puérperas da rede pública de saúde - Martins, Larissa Santos (2022)
Assessing maternal satisfaction with breastfeeding is one of the ways of evaluating the success of breastfeeding, taking into account the woman's perception and meeting the mutual needs of mother and baby. However, little is known about the breastfeeding satisfaction of low-income mothers and its associated factors. The aim was therefore to assess the level of maternal satisfaction with breastfeeding and its associated factors. This is a cross-sectional, observational study of mothers over 18 years of age, 30 to 180 days postpartum, who underwent the heel prick test at the Basic Health Units in Aracaju, Sergipe. Sampling was by convenience, based on the contacts available on the heel prick test list. Data was collected by telephone and the Maternal Breastfeeding Evaluation Scale (MBES) was used to assess maternal satisfaction with breastfeeding, as well as a semi-structured questionnaire with socio-economic, pregnancy, childbirth and puerperium data. The outcome was greater satisfaction, based on a score equal to or above the MBFES median. The chi-square or Fisher's exact test was calculated, with the application of the Odds Ratio and 95% confidence intervals, in order to find out the relationship between the outcome and the variables of interest. In the multivariate analysis, a logistic regression model was built, with intra-block analysis. A total of 291 puerperal women took part, with a median satisfaction with breastfeeding of 128 points, a minimum of 67 and a maximum of 145 points. In the multivariate analysis, in the distal block, greater satisfaction was associated with family income of less than one minimum wage (OR=2.12, 95%CI: 1.20- 3.74), in the intermediate block, the number of adequate prenatal consultations (OR=2.63, 95%CI: 1.01-6.85) and, from the proximal block, the absence of difficulty breastfeeding (OR=2.13, 95%CI: 1.21-3.75), current exclusive breastfeeding (OR=1.76, 95%CI: 1.04-2.99) and help with caring for the child during meals (OR=1.83, 95%CI: 1.01-3.31). Satisfaction with breastfeeding among puerperal women was high, and those with lower purchasing power, adequate prenatal care, breastfeeding exclusively and without difficulties and who had a support network had higher levels of satisfaction.